Effectiveness and safety of ranibizumab in a university hospital - Daniel Ribeiro; Lúcia de Araújo Costa Beisl Noblat (Instituto Nacional de Assistência Farmacêutica e Farmacoeconomia, 2024)
Purpose: To evaluate the effectiveness and safety of ranibizumab in the treatment of retinal diseases in a university hospital. Methods: Data from patients treated with ranibizumab were collected through participant interviews and medical records. The main measures of effectiveness were variations in visual acuity (VA) and changes in central retinal thickness (CRT). All adverse events that occurred during treatment were recorded for safety assessment. Results: A total of 103 patients, representing 154 eyes, were included in the study. The mean variation in VA was a loss of 0.9 letters on the ETDRS scale, and the mean variation in the CRT was a reduction of 12.6 µm. Conclusions: Considering the relatively limited changes in VA and CRT measurements, ranibizumab showed a lower degree of effectiveness in the treatment of neovascular diseases of the retinas. Low quantity and the interval between applications may have contributed significantly to the low effectiveness. The vast majority of adverse events reported were related to the medication application procedure.